2018
DOI: 10.4102/phcfm.v10i1.1612
|View full text |Cite
|
Sign up to set email alerts
|

The management of diabetic ketoacidosis at a rural regional hospital in KwaZulu-Natal

Abstract: BackgroundDiabetic ketoacidosis (DKA) is a biochemical triad of hyperglycaemia, ketoacidosis and ketonaemia and one of the potentially life-threatening acute metabolic complications of diabetes mellitus. This study aimed at describing the clinical profile of patients presenting with DKA to a busy rural regional hospital in KwaZulu-Natal.MethodsA retrospective review of clinical notes of patients presenting with DKA to the Emergency Department was performed over a 10-month period. Data included patients’ demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
3
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 48 publications
6
24
3
2
Order By: Relevance
“…DKA is considered a typical manifestation of T1D. With A previous report of DKA in MODY and T2DM, it is now believed that DKA can occur in all forms of diabetes (17). In the present study, an NDM case exhibited DKA and hyperglycemic hyperosmolar status, but the pathogenic variant group had a lower DKA incidence than the other groups (14 vs. 75 vs. 83.33%), suggesting that DKA incidence is lower in non-T1D cases.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…DKA is considered a typical manifestation of T1D. With A previous report of DKA in MODY and T2DM, it is now believed that DKA can occur in all forms of diabetes (17). In the present study, an NDM case exhibited DKA and hyperglycemic hyperosmolar status, but the pathogenic variant group had a lower DKA incidence than the other groups (14 vs. 75 vs. 83.33%), suggesting that DKA incidence is lower in non-T1D cases.…”
Section: Discussioncontrasting
confidence: 40%
“…In recent years, an increasing number of ketoacidosis cases without precipitating cause have been reported in children and adults with T2DM (17). It is difficult to determine the type of diabetes in the initial diagnosis of these people.…”
Section: Discussionmentioning
confidence: 99%
“…South Africa (30)and Bangladesh (31) revealed that infection was the major precipitant of DKA. Our finding also showed that urinary tract infection 24(47.05%) was the most common infection that precipitated DKA and our result was supported with a research evidence obtained in Jimma (10),…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 18 ] However, studies from different developing countries have revealed mortality rates as high as 10%–30% for patients hospitalized for DKA. [ 19 20 21 22 ]…”
Section: Introductionmentioning
confidence: 99%